Gender differences in functional somatic disorders of indigenous adolescents in Khakassia - Natalya Yu. Grishkevich; Lidia S. Evert; Svetlana A. Bakhshieva; Yuliya R. Kostyuchenko (Russian Open Medical Journal)
Rationale — The goal of the study was to investigate gender characteristics of functional somatic disorders in adolescents of the indigenous population of Khakassia (using the case study of the Abakan city). Material and methods — The object of the study was 215 (46.8%) boys and 244 (53.2%) girls of four secondary schools in Abakan. Their average age was 14.5±1.3 years. Data collection was conducted by means of an original screening questionnaire developed by Professor S.Yu. Tereshchenko. Results — The incidence of recurrent pain in the total sample of the surveyed youths was 184 (40.1%) for cephalalgia, 225 (49.0%) for abdominal pain, and 269 (58.7%) for back pain. The prevalence and structure of functional somatic disorders in Khakas adolescents depended on their gender. Asthenic syndrome was more common among girls – 42 (17.2%) vs. 14 (6.5%) in boys. In girls, the percentage of frequent headaches was higher than in boys: 22 (9.0%) vs. 8 (3.7%), respectively. Similar trend was observed in case of rare headaches: 100 (41.0%) vs. 54 (25.1%). Also, girls, compared with boys, were characterized by a higher incidence of both frequent and rare abdominal pains: 38 (15.6%) vs. 9 (4.2%) and 106 (43.4%) vs. 72 (33.5%), correspondingly. Conclusion — The case study of surveyed ethnic sample of Abakan school students revealed a high prevalence of recurrent pain syndromes in the indigenous youths of Khakassia. We have also established that incidence, structure and severity of recurrent pain, as well as its negative impact on well-being and daily activities, were associated with gender.